A Simple Introduction to Capital Expenditure Decisions - Garbutt, Douglas (London : Pitman, 1967)
The book explores the accounting and other measures of profitability, such as the pay-out plot, since many students and managers come to D.C.F. with set ideas about profitability and they need to be shown how and why these other measures are inadequate if, indeed, they are.
Bibliography: p. 130.
osc 13/06/17
Loans
Keywords: Capital investments